A Survey of Nicotine Yields in Small Cigar Smoke: Influence of Cigar Design and Smoking Regimens. Issue 10 (27th September 2017) - Goel, Reema; Trushin, Neil; Reilly, Samantha M; Bitzer, Zachary; Muscat, Joshua; Foulds, Jonathan; Richie, John P
Abstract: Introduction: Although the popularity of small cigar brands that resemble cigarettes, including both little cigars (LC) and filtered cigars (FC), has been on the rise, little is known about the delivery of nicotine from these products. Our objective was to determine the nicotine yields of small cigars in comparison to cigarettes. Methods: Nicotine yields from LC, FC, and 3R4F and 1R6F research cigarettes were determined from mainstream smoke generated on a smoking machine under the International Organization of Standardization (ISO) and Canadian Intense (CI) methods. Market characteristics (price and package label) and physical features (filter ventilation, product weight and filter weight, product length, and diameter) were also determined for eight brands of small cigars. Results: Nicotine yields in small cigars averaged 1.24 and 3.49 mg/unit on ISO and CI regimens, respectively, compared with 0.73 and 2.35 mg/unit, respectively, for the research cigarettes. Nicotine yields per puff were similar between small cigars and cigarettes. We also found that FC did not differ from LC in nicotine yields. FC and LC differ from each other in many physical design features (unit weight, filter weight, and filter length), but are similar in others (unit length, diameter, and filter ventilation). Conclusions: Nicotine delivery from small cigars is similar to or greater than that from cigarettes. Thus, for future research and regulatory purposes, standard definitions need to be developed for small cigars, and FC and LC should be evaluated as separate entities. Implications: Small cigars are similar to cigarettes in their design and use. Although nicotine yields per puff were similar between products, small cigars delivered substantially higher amounts of nicotine per unit than cigarettes. These findings support the growing body of evidence to justify regulating all small cigars, including LC and FC in a similar fashion as cigarettes.